Assessment of some behavioural patterns of a sheep flock on pasture - Filipcik, Radek; Hanzlikova, Katerina; Reckova, Zuzana; Hosek, Martin; Pesan, Vojtech; Kopec, Tomas (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
The aim was evaluated of annual ethological observation of sheep flock which took place on the pastures. There were observed these daily activities in the flock: grazing, laying and chewing, standing and chewing, locomotion, resting, standing and observing, drinking, comfortable behaviour, mineral lick intake. Within special behaviour which were observed only in particular season was sexual and maternal behaviour. The most frequently observed activity in winter was grazing with value of 49,18 %, in spring “laying and chewing“ with value of 63,03 %, in summer “grazing“ with value of 49,49 % and in autumn “grazing“ with value of 77,91 % from the total observed time. Significant differences (p<0.01) in the activities observed in sheep were demonstrated in different seasons in the case of grazing, lying down and chewing cud, and standing and chewing cud. On the basis of the balanced frequency of comfort behaviour demonstrated by the sheep during various seasons, we can state that the animals were kept in satisfactory conditions and their welfare requirements were met.